"A Cat's Paw of Indian Reactionaries"? Strategic Rivalry and Domestic Politics at the India–China–Myanmar Tri-Junction. Issue 1 (2nd January 2020) - Paliwal, Avinash
ABSTRACT: Ostensibly driven by concerns over a military standoff with China similar to Doklam, India increased military deployment at the Myanmar tri-junction. This article assesses the inevitability of systemic factors such as rivalry with China in determining India's approach on border issues. It asks why India sought formalization of its boundary with Burma in 1967. Given its territorial disputes with China, resolving the Burma boundary should have been high priority. Still, it took India two decades after independence to broach the subject. Based on fresh archival and interview data, this article answers the question by examining the India–Burma Boundary Agreement. A three-party territorial dispute, the making of this agreement witnessed simultaneous interplay between states with visible power differentials, and various stakeholders within India's polity and bureaucracy. The article argues that even when inter-state competition is apparent, domestic factors may be more important in triggering foreign policy change.